Precise delineation of radiation targets for thoracic tumors in the immunotherapy era: from immune mechanisms to clinical practice - Xiaoying Chen; Minxiao Yi; Yu Deng; Qian Shen (Precision Radiation Oncology, 2026)
Abstract As a core modality for local control of thoracic tumors, including lung and esophageal cancers, radiotherapy (RT) shows synergistic effects with immunotherapy, fundamentally reshaping the landscape of cancer treatment. Given the rapid advancements in immunotherapy, this review explores the critical role of precise delineation of radiotherapy targets in achieving synergistic effects between RT and immunotherapy. It elucidates the dual‐edged nature of RT, which can both activate antitumor immune responses and suppress immune function. Notably, larger radiation target volumes often cause destruction of tumor‐draining lymph nodes and reduce the number of peripheral blood lymphocytes, thereby impairing the efficacy of immunotherapy. To address this challenge, we discuss strategies tailored to thoracic tumors, including reducing target volumes, optimizing irradiation fields, and adjusting target positioning to protect key immune components. Furthermore, we highlight recent advancements in multimodal imaging, real‐time dynamic tracking technologies, and deep learning‐enabled automated segmentation methods that can increase the precision of target delineation. Additionally, emerging RT techniques, such as proton therapy and FLASH‐RT, demonstrate unique advantages in minimizing irradiation of normal tissues and circulating immune cells while enhancing immunomodulatory effects and thereby facilitating precise RT. This review aims to provide a theoretical foundation and technical support for accurate target delineation in the era of immunotherapy, particularly for thoracic malignancies, to promote the deep integration of RT and immunotherapy and improve patient outcomes.